THE ROLE OF ARTIFICIAL INTELLIGENCE IN ACTIVATING THE GLOBAL STOCK MARKET - Saif Alddin Imad Ahmed; Taib Othman Abdulrazzaq (Scholar Express Journals, 2025)
Artificial intelligence plays a significant role in supporting all fields, including financial aspects, as it plays a significant role in analyzing financial data and making appropriate decisions . The research problem was defined as how artificial intelligence affects the activation of the global stock market. The research is important through understanding the factors that determine the future and development of the global stock market, and how technology and artificial intelligence can integrate to achieve global financial goals. The research is based on the hypothesis that artificial intelligence plays a role in activating global stock market activity. The research is divided into three sections. The first section includes the theoretical framework of artificial intelligence, the second section contains the theoretical framework of global stock markets, and the third section includes artificial intelligence technology in activating global stock markets
Keywords: Artificial; Intelligence; Stock Market